Characterization of white-fleshed peach cultivars grown in the ‘Zona da Mata’ area of Minas Gerais State, Brazil - Silva, Danielle Fabíola Pereira da; Matias, Rosana Gonçalves Pires; Silva, José Osmar da Costa e; Salazar, Alejandro Hurtado; Bruckner, Claudio Horst (Comunicata Scientiae, 2016)
There are few information on the physical and chemical characteristics of peach fruit in subtropical climate regions and the majority of the studies were developed in the southern region of Brazil. In this study, physical and chemical characteristics of 12 white-fleshed peach cultivars (Cristal, Cristal Tacoari, Colibri, Delicioso Precoce, Jóia 1, Jóia 2, Jóia 4, Marli, Okinawa, Pérola de Itaquera, Premier and Tropical) were evaluated. The cultivars were planted in the experimental orchard of the Federal University of Viçosa (UFV), Viçosa – MG, Brazil. The experiment was conducted during the 2011 harvest season, in a completely randomized design with 12 treatments (cultivars), three replications and 10 fruits per plot. The cultivars Delicioso Precoce and Marli showed, in general, higher mass and fruit diameter. Fruits of cultivars Jóia 2 and Tropical presented higher firmness. Cultivar Tropical stood out with better balance between acidity and soluble solids and higher vitamin C and carotenoids contents.

Existem poucas informações sobre as características físicas e químicas de frutos de pessegueiro em regiões de clima subtropical, sendo a maioria dos trabalhos desenvolvidos na região Sul do Brasil. Desta forma, este trabalho objetivou avaliar características físicas e químicas de frutos de 12 cultivares de pessegueiro de polpa branca, a saber: Cristal, Cristal Tacoari, Colibri, Delicioso Precoce, Jóia 1, Jóia 2, Jóia 4, Marli, Okinawa, Pérola de Itaquera, Premier, Tropical. Elas foram introduzidas no pomar experimental da Universidade Federal de Viçosa (UFV), Viçosa-MG. O experimento foi conduzido durante a safra 2011, em delineamento inteiramente casualisado, com 12 tratamentos (cultivares), três repetições e 10 frutos por parcela. As cultivares Delicioso Precoce e Marli apresentaram, no geral, maior massa e diâmetros de frutos. Os frutos das cultivares Jóia 2 e Tropical apresentaram maior firmeza de polpa. Tropical se destacou por apresentar melhor balanço entre sólidos solúveis e acidez e maiores teores de vitamina C e de carotenoides.
Keywords: Adaptation; Prunus persica; Fruit quality; Adaptação; Prunus persica; Qualidade do fruto